Relationships Among Childhood Bullying, Academic Satisfaction, and Mental Health Outcomes in Adults with Disabilities - Bryan R. Christ; Bani Malhotra; Ghizlane Moustaid; Olivia Chapman; Paul B. Perrin (Diseases)
Purpose/Objective: Children with disabilities are at a greater risk of being bullied and experience mental health and academic problems that may persist in adulthood. This study examined the association of childhood bullying experiences with current mental health (anxiety and depression) among adults with disabilities, and whether academic satisfaction mediated the relationship between childhood bullying and adult mental health outcomes. Research Method/Design: A sample of 409 adult participants with disabilities who had had their disabilities while attending school, and currently, completed an online survey assessing bullying experiences (California Bullying Victimization Scale-Retrospective), academic satisfaction (Academic Satisfaction Scale), depression (Patient Health Questionnaire-9), and anxiety (Generalized Anxiety Disorder-7). Bivariate correlations and two mediation analyses were conducted to identify the direct and indirect effects of school bullying experiences on current mental health outcomes, via academic satisfaction. Results: Participants reported a moderate amount of childhood bullying and relatively high levels of depression and anxiety symptomology (with averages close to or exceeding clinical cutoffs of 10). Bivariate correlations among the four variables were all significantly moderately or strongly correlated. Bullying and academic satisfaction had direct associations with depression and anxiety. Academic satisfaction partially mediated the relationships between bullying and both mental health outcomes. Conclusions/Implications: Bullying prevention interventions and programs, especially geared toward preventing bullying in students with disabilities, are critical to stop the likely long-term impacts of bullying on mental health outcomes in disabled communities.